Three-dimensional porous tungsten via DLP 3D printing from transparent ink. (3rd November 2022) - Zan, Xiuqi; Wang, Xinyu; Shi, Kaihua; Feng, Yan; Shu, Jun; Liao, Jun; Wang, Richu; Peng, Chaoqun; Magdassi, Shlomo; Wang, Xiaofeng
Abstract: Tungsten, an essential refractory metal material, has the characteristics of high melting and boiling points, high hardness, low expansion coefficient, and low vapor pressure. An indirect strategy to print three-dimensional (3D) refractory metal materials via digital light processing (DLP) followed by a post-treatment process was proposed. To analyze this strategy, a transparent ink with tungsten salts was developed, printed into a 3D precursor via DLP, and subsequently transited into 3D porous tungsten. The ultraviolet rheological properties and stability of the ink, transition process from the precursor to a 3D article, and the properties of the obtained 3D porous tungsten were investigated. This ink was preferable for DLP 3D printing, possessing consistency, stability and favorable absorbance at the wavelength of 385 nm. With increasing temperature, the weight of the tungsten salt in the 3D precursor decreased by 8.97% and was transited to tungsten oxide below 460 °C, reduced to pure nano-sized tungsten at approximately 700 °C, and finally sintered into porous articles. The organics initially contributed to polymerization during printing as well as reduction as a carbon reducer after pyrolysis. The pore size distribution of porous tungsten is nonlinear or multimodal, depending on the final sintering temperature. At 1200 °C, two distinct peaks are observed in the pore distribution curves of the products. At 1400 °C, the small pore as a whole decreases from approximately 100–1000 nm. Correspondingly, the relative density of the samples increased with temperature.